Meningkatkan Kepuasan Masyarakat Melalui Kualitas Pelayanan Di Kantor Kepala Desa “X” - Aai, Mustika; Rahmat, Yogie (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This study aims to analyze the effect of service quality on public satisfaction at the Village Head Office "X". The method used in this study is descriptive and quantitative, with a simple random sampling technique of 81 respondents. The results of the simple linear regression analysis show the regression equation Y = 13.703 + 0.741X. The constant of 13.703 indicates that if the service quality (X) is zero, public satisfaction (Y) remains at 13.703. The regression coefficient of 0.741 indicates that every one unit increase in service quality will increase public satisfaction by 0.741 units, which indicates a positive influence between the two variables. The t-test results obtained tcount = 9.184, greater than ttable = 1.99045 (α = 0.05; df = 79), so Ha is accepted and Ho is rejected, which means that service quality has a significant effect on public satisfaction. The correlation value of R = 0.738 indicates a strong relationship, while the R² value of 0.645 indicates that service quality contributes 64.5% to public satisfaction, while the remaining 35.5% is influenced by factors outside this research model. This study concludes that improving service quality can significantly increase public satisfaction at the Village Head's Office "X".